Fishing boats at anchor in Monterey Bay - Albert Walton DeRome:::Creator::::::::::::
Monterey clipper-type lamparas at anchor and, in far background, large purse seiner at dock, probably at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.).